Efeito da temperatura de ecossistemas aquáticos geotermais tropicais nas interações tróficas aquático-terrestre - Lopes, Arianny Sanches (2023)
One of the ways in which terrestrial and aquatic ecosystems are connected is through the input of energy received in the form of organisms that have part of their development in the aquatic environment and migrate to the terrestrial environment in adulthood. Thermal changes in these ecosystems can enable changes in the flow of organisms that connect them. Species that perform this flow are mainly ectothermic. Different studies have found that this group is particularly vulnerable to warming. With the impact of temperature changes, the components of the trophic interactions in which these individuals participate can have their dynamics altered by changes in the entire ecosystem via bottom up and top down effects. Therefore, in order to understand how the increase in temperature affects the dynamics of food chains in riparian communities, we used thermal water streams as a natural experiment. The biological groups chosen were aquatic invertebrates, spiders, ants and other terrestrial invertebrates (herbivores). Samples were taken at three points with different temperatures in each of the seven streams. Our results suggest that temperature increase modifies aquatic-terrestrial trophic interactions. At points with water temperature above 41°C, the presence of aquatic invertebrates was not observed and, under these conditions, there was a drastic drop in the richness and abundance of spiders. These results demonstrate that the abundance and richness of spiders in the riverside environment is strongly determined by bottom up forces (via aquatic prey). Temperature also exerted a direct effect on the abundance of ants and spiders, however the effect was not deleterious as observed in aquatics. For terrestrial herbivores, temperature does not appear to have had an effect on their abundance. The abundance of ants proved to be strongly associated with terrestrial prey, in view of this, we can suggest that the use of the resource in a different way reduced the possible intra-guild competition between the two groups of predators.